Needle Stick Injuries among health care workers in a tertiary care hospital in District Bathinda, Punjab - Lal, Dhruvendra; Sidhu, Tanvir K; Coonar, PP S; Singh, Gurkirat (Indian Journal of Community Health, 2017)
Background: Because of the environment in which health care staff works, many they are at an increased risk of accidental needle stick injuries (NSI). NSI has been recognized as one of the potential occupational hazards for healthcare workers which results in transmission of blood borne pathogens such as HBV, HCV, and HIV/AIDS while performing their clinical activities in the Hospital. Aims & Objectives: To study the prevalence of needle stick injuries and knowledge and behavior of health care workers in a tertiary care centre. Material and Methods: A Hospital based cross sectional study was conducted among Health Care workers at a tertiary care hospital in 2016 at District Bathinda, Punjab. Results: A total of two hundred and eight (208) participants took part in the study from various departments. 58 health workers out of 208 i.e. 27% had NSI in the last 12 months. 84.1% of the health care workers were aware of the fact that HIV could transmitted by needle-stick injuries. While 55.8% and 83.2% knew that HBV and HCV respectively be transmitted through NSI. Only 46.6% of the health workers remembered that they had ever received HBV vaccination. Conclusions: The survey found out that the knowledge regarding the risk associated with NSI and use of preventive measures was adequate among the heath care workers but still there was a slight room for improvement in their attitude and practice and the same can be addressed through proper education and training